Electrically-switchable gain in optically pumped CsPbBr3 lasers with low threshold at nanosecond pumping - Yang, Li; Liu, Shangpu; Feeney, Thomas; Roger, Julie; Gholipoor, Mohammad; Hu, Hang; Zhao, Dewei; Howard, Ian; Deschler, Felix; Lemmer, Uli; Paetzold, Ulrich Wilhelm (Small, 2025)
Metal halide perovskites hold promise for nonepitaxial laser diodes, yet, continuous-wave (CW) optically pumped (photonic) lasing in CsPbBr3 remains elusive despite its superior thermal- and photo-stability among the perovskite family. This work reports on CsPbBr3 vertical cavity surface emitting lasers with low lasing thresholds (1.3 µJ cm− 2) at nanosecond pumping and remarkable lasing stability. Furthermore, the electrically switchable gain is achieved in CsPbBr3 electrically assisted optically pumped laser (EAOPL) devices by leveraging ion migration. Applying a small positive DC voltage to the EAOPL device significantly reduces the lasing threshold under nanosecond laser excitation and enhances the cavity mode intensity at CW laser excitation. These findings present a novel strategy, combining a small DC voltage with an electrical pulse, for exploring electrical injection lasing in CsPbBr3 perovskites.
Gesehen am 26.08.2025